Univerbizované názvy jevů prezentovaných v médiích a v publicistických textech - Kolářová, Ivana (Stylistyka, 2010)
Univerbization (or condensing) - fusing of multiverbal lexemes into one-word lexemes - is a word-forming process that is frequently used not only in contemporary spoken Czech texts, but also in the written texts. Linguistic research in the last 40-50 years proved that “univerbizates” are used in the joumalistic and media texts very often. The aim of the paper is to present univerbizates naming phenomena of the media and phenomena that are described in the media texts - names of persons (professions, performers), of actions and operations, names of films, plays or songs and compositions. The Czech national corpus has been used for this purpose. Results of the research are as follows - morę than 90 % univerbizates are formed by suffixation, of which nearly 75% - with the use of the -ak or -ka suffixes. They occur in various literary and colloąuial texts.